Long-term stability of oxidative stress biomarkers in human serum - Jansen, Eugene; Beekhof, Piet; Viezeliene, Dale; Mužáková, Vladimíra; Skalický, Jiri (My University, 2017)
The storage time and storage temperature might affect stability of oxidative stress biomarkers, therefore, they have to be analyzed after long-term storage of serum samples. The stability of three biomarkers reflecting oxidative stress: reactive oxygen metabolites (ROM) for hydro peroxides, total thiol levels (TTL) for the redox status and biological antioxidant potency (BAP) for the antioxidant status, was investigated at several time points during 60 months of storage at -20 and -80°C. Biomarkers ROM and BAP showed a very good stability during storage for 60 months at both temperatures. In addition, the correlation of the data after 60 months of storage compared with the starting data was very good with correlation coefficients >0.9. The TTL assay showed good results in serum samples stored at -80°C, but not in samples stored at -20°C. Serum samples for analysis of the set of oxidative stress biomarkers ROM, BAP and TTL can be stored up to 60 months at -80°C. ROM and BAP can also be stored at -20°C during this period. The present results are very important for the biomarker-related epidemiological studies that make use of biobanks with samples stored for many years and for new project planning, including sample storage conditions.
Dlouhodobá stabilita biomarkerů oxidačního stresu v lidském séru
Keywords: Long-term stability; oxidative stress biomarkers; human serum; Dlouhodobá stabilita; biomarkery oxidačního stresu; lidské sérum